2014
DOI: 10.1523/jneurosci.0311-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Regulation of Oligodendrocyte Development by Wnt/ -Catenin Signaling

Abstract: Oligodendrocytes are myelin-forming glia that ensheath the axons of neurons in the CNS. Recent studies have revealed that Wnt/␤-catenin signaling plays important roles in oligodendrocyte development and myelin formation. However, there are conflicting reports on the specific function of Wnt signaling components in oligodendrocyte specification and differentiation. In the present study, we demonstrate that activation of ␤-catenin in neural progenitor cells before gliogenesis inhibits the generation of oligodend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 29 publications
4
75
1
Order By: Relevance
“…Interestingly this complex signaling pathway exhibits differential and sometimes opposite effects on neural progenitor cell fate choice (Azim et al, 2014a,b). On the other hand, this pathway stimulates myelin gene expression in late differentiated cells (Tawk et al, 2011;Dai et al, 2014). In line with this, Azim and Butt demonstrated that GSK3-b inhibition promotes oligodendroglial cell differentiation and improves CNS remyelination process (Azim and Butt, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…Interestingly this complex signaling pathway exhibits differential and sometimes opposite effects on neural progenitor cell fate choice (Azim et al, 2014a,b). On the other hand, this pathway stimulates myelin gene expression in late differentiated cells (Tawk et al, 2011;Dai et al, 2014). In line with this, Azim and Butt demonstrated that GSK3-b inhibition promotes oligodendroglial cell differentiation and improves CNS remyelination process (Azim and Butt, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…In keeping with this interpretation, SVZ stem cells express high levels of the Egf receptor (Egfr, ErbB1), whereas OPCs do not (Chojnacki and Weiss 2004;Sun et al 2005;Cahoy et al 2008), and Egf has been reported not to stimulate proliferation of OPCs or other neural cells outside of the SVZ in slice culture (Hill et al 2013). (Canoll et al 1996;Vartanian et al 1999;Fernandez et al 2000;Carteron et al 2006;Brinkmann et al 2008;Taveggia et al 2008;Ortega et al 2012), Wnts (Shimizu et al 2005;Fancy et al 2009;Ye et al 2009;Langseth et al 2010;Dai et al 2014), neurotrophin-3 Cohen et al 1996), chemokines (Robinson et al 1998;Dziembowska et al 2005;Göttle et al 2010), ciliary neuronotrophic factor ), brain-derived neurotrophic factor (Vondran et al 2010;Wong et al 2013), transferrin (Silvestroff et al 2013), erythropoetin (Sugawa et al 2002), thyroid hormone (TH; triiodothyronine) (Walters and Morell 1981;Barres et al 1994;Ahlgren et al 1997;Rodriguez-Pena 1999), retinoic acid (Barres et al 1994;Noll and Miller 1994), and others. Most of these factors influence the differentiation of OLs and/or their subsequent survival including, perhaps especially, during demyelination and remyelination.…”
Section: Control Of Ol Development By Polypeptide Growth Factorsmentioning
confidence: 87%
“…Tcf7l2 and β-catenin form a transcriptional complex that inhibits differentiation, although the direct targets of this complex in the OL lineage likely include the inhibitory Id2 (Ye et al 2009), as is the case in carcinoma cells (Rockman et al 2001). Nevertheless, OL differentiation is reduced rather than enhanced in Tcf7l2 null mice (Fu et al 2009; Ye et al 2009) and delayed in mice in which β-catenin is inactivated in the OL lineage (Dai et al 2014), indicating that the roles of the β-catenin and Tcf7l2 are more complex than simply mediating the inhibitory effects on Wnt signaling. This could be partially explained by Tcf7l2 interacting with histone deacetylases HDAC1 and HDAC2 following down-regulation of Wnt signaling and β-catenin degradation (see below), thus repressing rather than activating the expression of inhibitors of differentiation (Ye et al 2009).…”
Section: Transcription Factors In Opcsmentioning
confidence: 99%
“…This could be partially explained by Tcf7l2 interacting with histone deacetylases HDAC1 and HDAC2 following down-regulation of Wnt signaling and β-catenin degradation (see below), thus repressing rather than activating the expression of inhibitors of differentiation (Ye et al 2009). In addition, the role of Wnt/β-catenin signaling may be highly stage specific, inhibiting specification, promoting some aspects of differentiation, but ultimately needing to be down-regulated for full differentiation (Dai et al 2014). …”
Section: Transcription Factors In Opcsmentioning
confidence: 99%